The introduction of decorative bulbs in Slovenia - Marko DOBRILOVIČ (Acta Agriculturae Slovenica, 2009)
This paper presens a comparative study of the introduction of the tulip in Slovenia and in Europe. The method is based on the investigation of archival material, provincial chronicles, and descriptive accounts. The goal of the research is to establish as precisely as possible the structure and form of gardens where decorative bulbs were planted, the habits of the owners of such gardens, and their relationships with each other. The second part of the research paper will present a comparison of the types of tulips found in Slovenian and foreign gardens in the 17th century. At the centre of the research project is the assortment of tulips from the park at Castle Lisičje, the first and most extensive collection of tulips in Slovenia dating from the mid-17th century. On the basis of comparisons with contemporaneous foreign tulip collections, we evaluated the collections in terms of the origin of various types and provide a description of prevailing social and economic factors. On the basis of the evaluation of this collection, it is possible to strongly support the hypothesis that the introduction of decorative bulbs (and particularly tulips) in Slovenia did not lag far behind the rest of Europe.